Outcome of a Mix-and-Match Approach with a Monofocal Aspherical and a Bifocal Extended Depth-of-Focus Intraocular Lens to Achieve Extended Monovision in Cataract Patients - Nagyova, Dana; Tappeiner, Christoph; Blaha, Andrej; Goldblum, David; Kyroudis, Dimitrios (Klinische Monatsblätter für Augenheilkunde, 2025)
Background Extended monovision is a novel mix-and-match approach that has been recently introduced. It involves implanting an aspherical monofocal intraocular lens (IOL) for distance vision in the dominant eye, and a bifocal extended depth-of-focus (EDOF) IOL in the nondominant eye. The target refraction for the nondominant eye is − 1.25 diopters (D), and provides good intermediate vision at 80 cm, with an additional 1.5 D power for near vision at 36 cm. This study evaluates the visual outcomes and patient-reported experiences with this extended monovision strategy in cataract patients.Patients and Methods Patients underwent uneventful conventional or femtosecond laser-assisted cataract surgery and implantation of an aspherical monofocal IOL (Hoya Vivinex XC1-SP, Hoya Surgical Optics, Tokyo, Japan) in the dominant eye [with a target refraction closest to the spherical equivalent (SE) of 0 D] and a rotationally asymmetric refractive bifocal EDOF IOL with an additional power of + 1.5 D (Lentis Comfort-LS-313 MF15, Teleon Surgical B.V, Spankeren, Netherlands) in the nondominant eye (target refraction closest to SE − 1.25 D). These patients were included in this retrospective study. Uncorrected distance, intermediate and near visual acuity (UDVA, UIVA, and UNVA, respectively), and binocular defocus curves were determined. Additionally, uncorrected contrast sensitivity, stereoscopic depth perception, and halometry were measured. Patient satisfaction was evaluated using the PRSIQ and NEI-RQL-42 questionnaires.Results A total of 26 eyes from 13 patients were included in the study. The mean postoperative binocular UDVA, UIVA, and UNVA were 0.05 ± 0.09, − 0.08 ± 0.11, and 0.06 ± 0.07 logMAR, respectively. The defocus curve peaked at 0.0 D (6 m), with a mean visual acuity of 0.04 ± 0.09 logMAR. Functional vision above the cutoff value of 0.3 logMAR extended across the defocus steps from + 1.0 to − 3.5 D. The mean dependence on correction score reached a mean of 89.4 ± 23.9, with an overall satisfaction rate of 83.1 ± 13.2.Conclusions To our knowledge, this is the first study to describe the combination of a monofocal IOL for distance vision and a rotationally asymmetric refractive bifocal EDOF IOL for intermediate and near distances, with the aim of achieving extended monovision. This approach demonstrated good visual acuity for all distances and a high patient satisfaction. It may be considered a promising alternative to multifocal IOLs.
Keywords: extended monovision; aspheric monofocal IOL; rotationally asymmetric bifocal extended depth-of-focus (EDOF) IOL; visual quality; patient-reported outcomes